EDNRB mutations cause Waardenburg syndrome type II in the heterozygous state. Issue 5 (15th March 2017) - Issa, Sarah; Bondurand, Nadege; Faubert, Emmanuelle; Poisson, Sylvain; Lecerf, Laure; Nitschke, Patrick; Deggouj, Naima; Loundon, Natalie; Jonard, Laurence; David, Albert; Sznajer, Yves; Blanchet, Patricia; et al.
Abstract : We performed exome sequencing and cohort screening in Waardenburg syndrome type II (WS2), characterized by sensorineural hearing loss and pigmentation anomalies. Despite prior involvement of MITF and SOX10, most cases remain unexplained. We identified 6 heterozygous EDNRB variations that resulted in loss‐of‐function by in vitro functional studies. Clinical and molecular investigations unraveled a dominant mode of inheritance with incomplete penetrance. Abstract: Waardenburg syndrome (WS) is a genetic disorder characterized by sensorineural hearing loss and pigmentation anomalies. The clinical definition of four WS types is based on additional features due to defects in structures mostly arising from the neural crest, with type I and type II being the most frequent. While type I is tightly associated to PAX3 mutations, WS type II (WS2) remains partly enigmatic with mutations in known genes ( MITF, SOX10 ) accounting for only 30% of the cases. We performed exome sequencing in a WS2 index case and identified a heterozygous missense variation in EDNRB . Interestingly, homozygous (and very rare heterozygous) EDNRB mutations are already described in type IV WS (i.e., in association with Hirschsprung disease [HD]) and heterozygous mutations in isolated HD. Screening of a WS2 cohort led to the identification of an overall of six heterozygous EDNRB variations. Clinical phenotypes, pedigrees and molecular segregation investigations unraveled a dominant mode of inheritance with incomplete penetrance. In parallel, cellular and functional studies showed that each of the mutations impairs the subcellular localization of the receptor or induces a defective downstream signaling pathway. Based on our results, we now estimate EDNRB mutations to be responsible for 5%–6% of WS2.